Journal of the American Statistical Association. - American Statistical Association ([New York] : American Statistical Association, 1922)
Print + Online (from 1997-)
Title from cover.
Keywords: Statistics -- Periodicals; Statistics -- Periodicals; Statistiek; Statistique -- Périodiques.; STATISTICAL METHODOLOGY